Noncytotoxic differentiation treatment of renal cell cancer - Negrotto, Soledad (2011)
Current drug therapy for metastatic renal cell cancer (RCC) results in temporary disease control but not cure, necessitating continued investigation into alternative mechanistic approaches. Drugs that inhibit chromatin-modifying enzymes involved in transcription repression (chromatin-relaxing drugs) could have a role, by inducing apoptosis and/or through differentiation pathways. At low doses, the cytosine analogue decitabine (DAC) can be used to deplete DNA methyl-transferase 1 (DNMT1), modify chromatin, and alter differentiation without causing apoptosis (cytotoxicity). Noncytotoxic regimens of DAC were evaluated for in vitro and in vivo efficacy against RCC cell lines, including a p53-mutated RCC cell line developed from a patient with treatment-refractory metastatic RCC. The cell division - permissive mechanism of action - absence of early apoptosis or DNA damage, increase in expression of HNF4α (hepatocyte nuclear factor 4a), a key driver associated with the mesenchymal to epithelial transition, decrease in mesenchymal marker expression, increase in epithelial marker expression, and late increase in cyclin-dependent kinase inhibitor CDKN1B (p27) protein - was consistent with differentiation-mediated cell-cycle exit. In vivo blood counts and animal weights were consistent with minimal toxicity of therapy. The distinctive mechanism of action of a dose and schedule of DAC designed for noncytotoxic depletion of DNMT1 suggests a potential role in treating RCC. ©2011 AACR.